2017
DOI: 10.1186/s13613-017-0244-y
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin use and 28-day in-hospital mortality among severe-burn patients: an observational nationwide study

Abstract: BackgroundPrevious studies have suggested that antithrombin may be beneficial for treating coagulopathy in patients with severe burns. However, robust evidence for this idea is lacking. We examined the hypothesis that antithrombin may be effective in treating patients with severe burns.MethodsWe performed propensity score-matched analyses of the nationwide administrative Japanese Diagnosis Procedure Combination inpatient database. We identified patients with severe burns (burn index ≥ 10) who were recorded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
(81 reference statements)
0
23
0
Order By: Relevance
“…Several similar ‘unique evolution’ drugs, including antithrombin administration for DIC , recombinant human soluble thrombomodulin for DIC and intravenous immunoglobulin for sepsis , were previously evaluated using the Japanese Diagnosis Procedure Combination (DPC) database. Several experimental studies have suggested that these drugs are pharmacologically appropriate for the treatment of each pathophysiological condition.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Several similar ‘unique evolution’ drugs, including antithrombin administration for DIC , recombinant human soluble thrombomodulin for DIC and intravenous immunoglobulin for sepsis , were previously evaluated using the Japanese Diagnosis Procedure Combination (DPC) database. Several experimental studies have suggested that these drugs are pharmacologically appropriate for the treatment of each pathophysiological condition.…”
mentioning
confidence: 99%
“…medications, drip infusions, and several procedures, including surgeries) and the starting dates and duration of each treatment during hospitalization. These data allowed us to clearly define inclusion and exclusion criteria in our studies . We believe that the DPC database is, at least currently, the best available nationwide database for evaluating the effect of treatments that are used only in Japan.…”
mentioning
confidence: 99%
See 3 more Smart Citations